Cannabis use among youth in Canada: a scoping review protocol. Issue 6 (20th June 2022) - Kourgiantakis, Toula; Edwards, Travonne; Lee, Eunjung; Logan, Judith; Vicknarajah, Ragave; Craig, Shelley L; Simon-Tucker, Monique; Williams, Charmaine C
Abstract : Introduction: Canadian youth (aged 15–24) have the highest rates of cannabis use globally. There are increasing concerns about the adverse effects of cannabis use on youth physical and mental health. However, there are gaps in our understanding of risks and harms to youth. This scoping review will synthesise the literature related to youth cannabis use in Canada. We will examine the relationship between youth cannabis use and physical and mental health, and the relationship with use of other substances. We will also examine prevention strategies for youth cannabis use in Canada and how the literature addresses social determinants of health. Methods and analysis: Using a scoping review framework developed by Arksey and O'Malley, we will conduct our search in five academic databases: MEDLINE, Embase, APA PsycInfo, CINAHL and Web of Science's Core Collection. We will include articles published between 2000 and 2021, and articles meeting the inclusion criteria will be charted to extract relevant themes and analysed using a qualitative thematic analysis approach. Ethics and dissemination: This review will provide relevant information about youth cannabis use and generate recommendations and gaps in the literature. Updated research will inform policies, public education strategies and evidence-based programming. Results will be disseminated through an infographic, peer-reviewed publication and presentation at a mental health and addiction conference. Ethics approval is not required for this scoping review.